2015
DOI: 10.1021/acs.biomac.5b00603
|View full text |Cite
|
Sign up to set email alerts
|

Positively Charged Chitosan and N-Trimethyl Chitosan Inhibit Aβ40 Fibrillogenesis

Abstract: Amyloid fibrils, formed by aggregation of improperly folded or intrinsically disordered proteins, are closely related with the pathology of a wide range of neurodegenerative diseases. Hence, there is a great deal of interest in developing molecules that can bind and inhibit amyloid formation. In this regard, we have investigated the effect of two positively charged polysaccharides, chitosan (CHT) and its quarternary derivative N-trimethyl chitosan chloride (TMC), on the aggregation of Aβ40 peptide. Our aggrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 60 publications
3
46
0
Order By: Relevance
“…Chitosan‐decorated nanomaterials have currently been applied to the delivery of peptides, proteins, small molecules, genes, and multitheranostics drugs for satisfactory biodegradability, biocompatibility, and non‐immunogenicity in chitosan . Earlier studies also reported that chitosan and its derivative could inhibit the fibrillogenesis of amyloid β‐protein Aβ‐40 and/or age‐related diseases . Based on these properties, we tried to incorporate chitosan oligosaccharide lactate with E 6 Q 10 to increase interactions with the cell membrane and facilitate cell delivery.…”
Section: Resultsmentioning
confidence: 99%
“…Chitosan‐decorated nanomaterials have currently been applied to the delivery of peptides, proteins, small molecules, genes, and multitheranostics drugs for satisfactory biodegradability, biocompatibility, and non‐immunogenicity in chitosan . Earlier studies also reported that chitosan and its derivative could inhibit the fibrillogenesis of amyloid β‐protein Aβ‐40 and/or age‐related diseases . Based on these properties, we tried to incorporate chitosan oligosaccharide lactate with E 6 Q 10 to increase interactions with the cell membrane and facilitate cell delivery.…”
Section: Resultsmentioning
confidence: 99%
“…Eqn (29) allows us to test the validity of the lag time expression under different conditions of the ratio of reactant in excess to limiting reactant (m 0 to f 0 *), given that the conditions, eqn (26) and (28), for the reactant stationary approximation are met. With m 0 fixed to one and the length n fixed, for large values of f 0 *, such that a o 10, the percentage of the maximum product reached at the lag time increases very rapidly and the excess monomer condition is unstable.…”
Section: Monomer In Excess and Fibril Template As The Limiting Reactantmentioning
confidence: 99%
“…Eqn (1) and variations thereof are often used to estimate the empirical parameters for progress curves of protein aggregation experiments. [24][25][26] The lag time (t lag ) is typically estimated by extending the tangent at t m to the initial baseline. The lag time is then given in terms of the empirical parameters:…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of cationic biopolymers such as chitosan (CHT) and N-trimethyl chitosan (TMC, quaternary derivative) with A (1 − 40) has been reported. 54 The charge density of CHT is dependent on solution pH, while TMC always holds a positive charge irrespective of changes in pH. At neutral pH (7.4), the inhibitory activity of CHT and TMC on A (1 − 40) fibrillogenesis is driven by electrostatic interaction between the CHT holding positive charges and the negatively charged aspartic acid and glutamic acid.…”
Section: Interactions Of Amyloids With Chitosanmentioning
confidence: 99%
“…The interaction of cationic biopolymers such as chitosan (CHT) and N ‐trimethyl chitosan (TMC, quaternary derivative) with Aβ(1 − 40) has been reported . The charge density of CHT is dependent on solution pH, while TMC always holds a positive charge irrespective of changes in pH.…”
Section: Interaction Of Amyloids With Natural and Artificial Polymersmentioning
confidence: 99%